Evaluation of YouTube videos on soft tissue sarcomas: How reliable are YouTube shares? - Yurtbay, Alparslan; Aydın Şimşek, Şafak; Cengiz, Tolgahan; Coşkun, Hüseyin Sina; Dabak, Nevzat (The European Research Journal, 2025)
Objectives: Soft tissue sarcomas of the musculoskeletal system account for approximately 8% of malignant tumors in adolescents and young adults. As the fight against cancer, a disease of our era, increases, this topic has become increasingly popular on social media. This study aims to investigate the quality and reliability of videos published on YouTube providing information on musculoskeletal soft tissue sarcomas. Methods: In the study, the 50 videos with the highest number of views, published on YouTube and providing information about soft tissue tumors of the musculoskeletal system, were evaluated and analyzed by two different observers. Observers scored the videos according to the DISCERN and JAMA scoring systems. Results: Of the 50 YouTube videos evaluated, the most extended video was 1 hour 29 minutes 28 seconds, while the shortest video was 45 seconds. The highest number of views was 145,122. Statistically significant high agreement was obtained between observers regarding DISCERN and JAMA scores (ICC=0.734 and P<0.01). When average DISCERN scores were evaluated, video content quality was 12% very poor, 56% poor, 26% average, and 6% good. Conclusions: Video content providing accurate and reliable information on soft tissue sarcomas should be created so patients can understand it, with proper references, and curated by healthcare professionals. Collaboration with healthcare professionals should be sought to enhance the quality and reliability of video content on YouTube.